A Hermeneutical Analysis on Fatwa of the Council of Indonesian Ulama Dealing with Discriminating Shia in Indonesia - Mukhsin Ahmad (Jurnal Madania)
The present article is aimed at analyzing the Council of Indonesian Ulama (MUI, Majelis Ulama Indonesia) fatwa on Shia in Indonesia. The decree of MUI fatwa should be described and analyzed due to potential powerful to influence Indonesian Muslim community. Besides, there are three dialectics of discovering the fatwa such as the author, the content, and the reader of fatwa. The effect of such decree tends to occur a violence among religious minority such as discrimination and intimidation. The process of producing fatwa does not properly consider five contingencies as the parameter of authoritative fatwa. According to MUI, Shia is one of the deviate belief systems in Indonesia because it has primary different doctrine from ten indicators. To avoid the authoritarianism of fatwa and violence against religious minority, MUI as an official institution who produces the fatwa should consider the five contingencies, namely honesty, diligence, reasonableness, comprehensiveness, and self restraint.